1994
DOI: 10.1128/jb.176.11.3295-3302.1994
|View full text |Cite
|
Sign up to set email alerts
|

Pullulanase of Thermoanaerobacterium thermosulfurigenes EM1 (Clostridium thermosulfurogenes): molecular analysis of the gene, composite structure of the enzyme, and a common model for its attachment to the cell surface

Abstract: The complete pullulanase gene (amyB) from Thermoanaerobacterium thermosulfurigenes EM1 was cloned in Escherichia coli, and the nucleotide sequence was determined. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 46 publications
0
69
0
1
Order By: Relevance
“…The SLH domain was postulated to be the determinant for interaction of the S-protein and other extracellular proteins with the underlying peptidoglycan layer (Matuschek et al, 1994). Another explanation is that the SLH domain of such extracellular enzymes interacts with (SLH) domains of the S-protein (Egelseer et al, 1995).…”
Section: Interaction Between S-proteins and Cell-wall Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SLH domain was postulated to be the determinant for interaction of the S-protein and other extracellular proteins with the underlying peptidoglycan layer (Matuschek et al, 1994). Another explanation is that the SLH domain of such extracellular enzymes interacts with (SLH) domains of the S-protein (Egelseer et al, 1995).…”
Section: Interaction Between S-proteins and Cell-wall Componentsmentioning
confidence: 99%
“…Although some particular functions could be assigned to specific S-proteins, such as barriers between the cell and the environment (Paula et al, 1988) and attachment structure for extracellular enzymes (Matuschek et al, 1994), no general function has been described which is found for all S-layers. For Archaebacteria, it has been reported that the S-layer plays a role in maintenance of the cell shape (Pum et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…8, part of the sequence of Amy is aligned with that of its three closests relatives [Tts and Tet, standing for the (amy1o)pullulanases from 7: thermosulfurigenes [26] and 7: ethanolicus [27], respectively, which are almost identical to the a-amylase pullulanase from 7: thermohydrosulfuricus [28], and Neo, the neopullulanase from B. stearothermophilus [50]]. In the aligned regions, Tts, Tet and Neo show 63, 60 and 56% sequence similarity with Amy, in which similarity is defined as the sum of the identical plus the conservatively exchanged residues (see the legend to Fig.…”
Section: Sequence Alignmentmentioning
confidence: 99%
“…Recently, Koivola et al [25] published the nucleotide sequence of this gene. Unexpectedly, its product is predicted to consist of as many as 1301 amino acid residues and to be closely related to a group of enzymes referred to as pullulanases, amylo-pullulanases, or a-amylases-pullulanases from Therrnoanaerobacterium thermosulfurigenes (formerly Clostridium thermosuljiurogenes) EM1 [26], Thermoanaerobacterium ethanolicus (formerly Clostridium thermohydosulfuricum) 39E [27] and Thermoanaerobacter (formerly Clostridium) thermohydrosulfuricum [28]. Koivola et al [25] did not isolate the A. acidocaldurius ATCC 27009 enzyme, but a zymogram shows that the main starch-degrading protein has an apparent molecular mass of 160000Da.…”
mentioning
confidence: 99%
“…Clostridium thermocellum, a thermophilic, anaerobic bacterium, is best known for producing highly active multienzyme cellulase complexes termed cellulosomes polysaccharides (Lupas et al, 1994;Matuschek et al, 1994). SLH domains appear to mediate attachment of proteins to the cell wall (Lemaire et al, 1995 ;Olabarria et al, 1996) as well as interactions with other SLH domains (Lemaire et al, 1995).…”
Section: Introductionmentioning
confidence: 99%